PENGARUH BRAND AMBASSADOR, KEPUASAN PELANGGAN DAN BRAND AWARENESS TERHADAP KEPUTUSAN PEMBELIAN PRODUK ACNE CARE SCARLETT WHITENING DI KELAPA GADING, JAKARTA UTARA - Cindy Alodia Pratama; Abdulah Rakhman (Sekolah Tinggi Pariwisata Mataram, 2022)
Along with the growth of the beauty industry in Indonesia, many local brands use Brand Ambassadors, increasing Customer Satisfaction and Brand Awareness in attracting consumers to make purchasing decisions for marketed products. This study aims to analyze how the influence of Brand Ambassador, Customer Satisfaction and Brand Awareness on Purchase Decisions. The data analysis technique used in this research is the pooling test, classical assumption test, descriptive statistical test, F test, t test and coefficient of determination test using SPSS 25.0. The results of this study indicate that brand ambassadors, customer satisfaction, and brand awareness have a positive and significant effect on purchasing decisions for acne care scarlett whitening in Kelapa Gading, North Jakarta.